Решите уравнение (x2 – 25)2 + (x2 + 2x – 15)2 = 0.
Источник: ЕГЭ ОГЭ по математике Под редакцией И.В. Ященко.
Решение:
(х2 – 25)2 + (х2 + 2х – 15)2 = 0
х2 – 25 = х2 – 52 = (х – 5) ∙ (х + 5)
х2 + 2х – 15 = 0
D = b2 – 4ac
D = 22 – 4 ∙ 1 ∙ (-15) = 4 + 60 = 64
√D = 8
x = (-b ± √D) / (2a)
х1 = (-2 + 8) / 2 = 6/2 = 3
х2 = (-2 – 8) / 2 = -10/2 = -5
х2 + 2х – 15 = (х – 3) ∙ (х + 5)
((х – 5) ∙ (х + 5))2 + ((х – 3) ∙ (х + 5)2 = 0
(х – 5)2 ∙ (х + 5)2 + (х – 3)2 ∙ (х + 5)2 = 0
(х + 5)2 ∙ ((х – 5)2 + (х – 3)2) = 0
1) (х + 5)2 = 0
х + 5 = 0
х = -5
2) (х – 5)2 + (х – 3)2 = 0
х2 – 10х + 25 + х2 – 6х + 9 = 0
2х2 – 16х + 34 = 0
х2 – 8х + 17 = 0
D = (-8)2 – 4 ∙ 1 ∙ 17 = 64 – 68 = – 4 < 0
Квадратное уравнение не имеет корней
Ответ: -5